2012
DOI: 10.1038/ijir.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaco-induced erections for penile color-duplex ultrasound: oral PDE5 inhibitors or intracavernosal injection?

Abstract: To prospectively compare the clinical responses and penile color-duplex ultrasound (PCDU) results of oral PDE5 inhibitors (PDE5-Is) with papaverine intracavernosal injection (ICI) and to evaluate whether PDE5-Is could be used as alternatives to vasoactive agent injections, 25 ED patients underwent PCDU three times with an interval of at least 1 week, using different pharmacological induction: ICI mode (30--60 mg papaverine), sildenafil mode (100 mg sildenafil) and tadalafil mode (20 mg tadalafil). The preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was found that the PSV value of proximal cavernous artery was much higher than that of distal cavernous artery in both ED patients (39.0±11.2 vs. 20.0±5.6 cm/s) and normal controls (39.8±8.0 vs. 21.3±5.5 cm/s) (55). There may also be differences in PSV values between the left and right cavernous arteries (58). A difference of more than 20 percent between the two arterial regions of the penis was considered suspicious of arterial insufficiency (39).…”
Section: Cddumentioning
confidence: 93%
“…It was found that the PSV value of proximal cavernous artery was much higher than that of distal cavernous artery in both ED patients (39.0±11.2 vs. 20.0±5.6 cm/s) and normal controls (39.8±8.0 vs. 21.3±5.5 cm/s) (55). There may also be differences in PSV values between the left and right cavernous arteries (58). A difference of more than 20 percent between the two arterial regions of the penis was considered suspicious of arterial insufficiency (39).…”
Section: Cddumentioning
confidence: 93%
“…also reported a significant difference in the number of patients able to reach full erection with ICI. Eighty percent of patients were able to reach full erection with ICI of papaverine, compared with 60% with sildenafil and 56% with tadalafil [31].…”
Section: Use Of Ici In the Diagnosis And Evaluation Of Edmentioning
confidence: 95%
“…Cavernous arterial diameters and haemodynamics were measured at baseline before pharmaco-induced erection and commonly every 5 min afterwards up to 20 min. Pharmaco-induced erection procedure (Yang et al, 2011(Yang et al, , 2012: patients were asked to take sildenafil (Viagra) 100mg 1 hr in advance. Audiovisual sexual stimulation (AVSS) and masturbation stimulation were synchronously given 15 min before the erection test.…”
Section: Cddu Testmentioning
confidence: 99%